Infant cancers in France: Incidence and survival (2000–2014). (April 2020) - Desandes, Emmanuel; Faure, Laure; Guissou, Sandra; Goujon, Stéphanie; Berger, Claire; Minard-Colin, Véronique; Petit, Arnaud; Schleiermacher, Gudrun; Poulalhon, Claire; Lacour, Brigitte; Clavel, Jacqueline
Highlights: The most frequent infant cancers: neuroblastomas (30 %), CNS tumors (16 %), leukemias (15 %), and retinoblastomas (12 %). Embryonal malignancies accounted for 55% of cases. Annual incidence rate, 243 per million infants overall, stable over the 2000-2014 period. 5-year overall survival (5-yOS) was 81 %, and 71 % of deaths occurred within the first month of life. Lowest 5-yOS (<65 %) observed for acute myeloid leukemias, CNS tumors, and lymphoid leukemias. Abstract: Background: On average 185 children are diagnosed each year in France with a cancer in their first year of life, representing 11 % of cancers diagnosed in children less than 15 years. Methods: A retrospective population-based observational study was conducted between 2000 and 2014 of all infants with a diagnosis of cancer using the National Registry of Childhood Cancers Database. Results: Out of 2760 cases of primary cancers in infancy, there were mainly neuroblastomas 30.1 %), central nervous system (CNS) tumors (16.1 %), leukemias (15.3 %), retinoblastomas (11.6 %), and Wilms tumors (6.9 %). Embryonal malignancies accounted for 55.2 % of cases. Most diagnoses showed a male excess, particularly for malignant gonadal germ-cell tumors (GCT) with a 17.5 sex-ratio. The annual incidence rate, 242.9 per million infants overall, was stable over the study period for all types of cancer. Most deaths occurred within the first month of life (70.8 % of deaths). The 5-year overall survival (5-y OS) was 81.0 % (95 %CI, 79.4–82.4) with large contrasts between diagnoses. The best 5-y OS (>85 %) were observed for retinoblastomas, carcinomas, nephroblastomas, GCT, neuroblastomas, and hepatoblastomas. Conversely, the lowest 5-y OS (<65 %) were observed for acute myeloid leukemias, CNS tumors, and lymphoid leukemias. We observed no substantial change over time (80.5 % [95 %CI, 77.7–82.9] in 2000–2004 and 82.6 % [95 %CI, 80.0–84.9] in 2010–2014) for all cancers combined. The same result has been found whatever the diagnostic group. Conclusion: Our results contribute to better understand these tumors by quantifying their impact on the French population and assessing the burden of some devastating infant cancers.